Pengaruh Pengetahuan Kewirausahaan dan Lokasi Usaha Terhadap Keberhasilan Usaha Pada UMKM Produk Wisatadi Kecamatan Bohorok, Kabupaten Langkat, Sumatera Utara - Br Surbakti, Nadya Faradila; Utama Nasution, Amrin Mulia (Economics, Business and Management Science Journal, 2025)
This study aims to determine the influence of entrepreneurial knowledge and business location on business success in tourism product MSMEs in Bohorok District, Langkat Regency, North Sumatra. This study is quantitative research with a purposive sampling technique, using the Slovin formula to determine the number of samples of 79 respondents. The sample consisted of MSME actors in tourism products who have been running a business for over 3 years and are 5-20 years old. Data were collected through questionnaires and observations, while data analysis was carried out by instrument tests, classical assumption tests, multiple regressions, and hypothesis tests using SPSS 27. The results of the partial test show that entrepreneurial knowledge and business location have a significant effect on business success. This is evidenced by the t-count value of 2,083 t table 1,991 (sig 0.041 0.05) for entrepreneurial knowledge and t count 4,357 t table 1,991 (sig 0.000 0.05) for business location. The simultaneous test also showed a significant influence between the two on the business's success with F count 13,312 F table 3,115 (sig 0.000 0.05). The value of the determination coefficient (R²) of 0.258 (25.8%) shows that the success of MSME businesses for tourism products in Bohorok District, Langkat Regency, North Sumatra, is influenced by entrepreneurial knowledge and business location, while 73.2% is influenced by other factors that were not studied in this study.